Upaya Meningkatkan Hasil Belajar Matematika Melalui Model Problem Based Learning Berbantuan Media Papan Magnet Diagram (Panetagram) Pada Siswa Kelas IV SD Negeri 3 Sokanegara - Ahyaningsih, Faiz; Yanuarto, Wanda Nugroho; Purwani, Purwani (UM Purwokerto Press, 2025)
This study aims to improve student learning outcomes through the application of the Problem Based Learning (PBL) learning model with the help of diagram magnet board media (Panetagram). This research is motivated by the low student learning outcomes in mathematics subjects caused by the lack of variety in learning methods. The uniqueness of this research lies in the integration of the Problem Based Learning model with the magnetic board diagram (panetagram) media in collaborative mathematics learning. This research is important to provide contextual solutions to the problem of low learning outcomes at the elementary school level, as well as contribute to the development of active and collaborative learning models. This research was conducted at the partner school during the implementation of PPL II, namely at SD Negeri 3 Sokanegara. This type of research is Classroom Action Research (PTK). Data collection methods used test techniques (evaluation questions), non-test techniques (teacher activity observation sheets and student activity observation sheets), and documentation. The research subjects were fourth grade students of SD Negeri 3 Sokanegara with a total of 30 students. The results showed an increase in students' math learning outcomes which can be seen from the results of the average score in cycle I 71.33 with a completion percentage of 53%. Math learning outcomes in cycle II obtained an average score of 87 with a completion percentage of 70%. The learning outcomes of cycle III obtained an average score of 98.67 with a percentage of 100% completeness with very good criteria. The results showed that the application of the Problem Based Learning (PBL) learning model assisted by the magnet board diagram (panetagram) media was very effective in improving the learning outcomes of mathematics class IV SD Negeri 3 Sokanegara in 2024/2025.